Beyond 'farmer first' - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Beyond farmer first: rural people's knowledge, agricultural research and extension practice edited by lan Scoones and John Thompson 1994 301pp ISBN 85339 250 2 published by IT Publications Ltd, 103-105 Southampton Row, London WC1B 4HH, UK Available